SPIDER BITES IN THE ARGENTINIAN ATLANTIC FOREST (2017-2023) (Boletín de la Sociedad Zoológica del Uruguay, 2024)
The aim of this work was to provide information on arachnidism in northern Misiones province. We used the database (2017-2023) of the National Institute of Tropical Medicine. We recorded 62 incidents, classified as mild, only one moderate. Phoneutrism was the most frequent intoxication (66%). We present the first case of Loxosceles hirsuta Melo-Leitão, 1931 bite. Cases occurred throughout the year, with peaks in November and May, and occurred mainly on the hands or feet. The main affected groups were residents aged 0 to 10 and 22-32 years. Female/male ratio = 0.51. Fifty-four percent of cases occurred at home and 29% in rural areas. Stinging pain and erythema were the most frequent local symptoms. Spider bites were not correlated with climatic variables and no seasonality was evident. Arachnidism in northern Misiones involves native and frequent spiders, and is possibly facilitated by local human habits and lifestyles. Taxonomic diagnosis was beneficial in determining and monitoring the assemblage of spiders of medical interest in the region.
Keywords: Epidemiology; Loxosceles; Phoneutria; Toxicology; Public health surveillance